3D evaluation of fetal brain structures: reference values and growth curves. (2nd November 2021) - Babucci, Giulia; Rosen, Karl; Cappuccini, Benito; Clerici, Graziano
Abstract: Background: The development of the fetal central nervous system is one of the most important fields of research in perinatology. Since the early 1980s, 3 D ultrasound has become one of the major research tools in obstetrics and gynecology. Objective: The aim of this study was to reconstruct thalamus, cerebellum and Cortex volumes of fetal brain and generate, for these volumes, growth curves related to gestational age. Methods: We enrolled 344 pregnant women. Using "Tomographic Ultrasound Imaging" (TUI), in all cases we obtained a satisfying 3 D acquisition of fetal brain. We reconstructed offline thalamus, cerebellum and cortex volumes using "Virtual Organ Computer-Aided AnaLysis" (VOCAL) or 4 D View (GE Healthcare). Results: Among the 344 fetuses examined, we obtained 314 thalamus volumes, 252 cerebellum volumes and 261 cortex volumes and we constructed the reference growth curves. Conclusion: Our study confirms the reliability of cerebral volumes evaluation using 3 D technology and how these cerebral structures grow through gestation.